Renal Dysfunction in Patients with Liver Cirrhosis - Sobh, Mahmoud; Abdalbary, Mohamed; Abdelsalam, Mostafa; Mohamed, Amr El-Husseini (Digestive Disease Interventions, 2022)
Liver cirrhosis is a major health problem that can affect people of different ages. It induces pivotal hemodynamic and metabolic systemic disturbances along with other organs dysfunction. Renal dysfunction in cirrhotic patients is not uncommon, and subtle renal impairment is an early and very frequent finding. Liver cirrhosis can afflict kidney functions through different mechanisms. Renal vasoconstriction is usually the initial response of splanchnic vasodilation and decreased effective renal plasma flow. This induces a reduction of intraglomerular pressure leading to stimulation of renin-angiotensin system to maintain the glomerular filtration rate. Other causes of renal dysfunction include electrolytes and acid-base disturbances, systemic inflammation, bile cast nephropathy, and intra-abdominal hypertension. Loss of renal reserve is usually the earliest manifestation of kidney dysfunction in cirrhotic patients. This makes the kidney supersensitive to any subsequent hemodynamic or metabolic abnormalities. Proper assessment of kidney function is one of the major challenges in cirrhotic patients. The use of serum creatinine and creatinine-based equations is inaccurate and can overestimate kidney function. Hepato-renal syndrome (HRS) is a life-threatening disorder. In the last decade, there was significant progress in understanding the mechanism of this mysterious disorder. In this article, we are focusing on different mechanisms of kidney dysfunction in cirrhotic patients and the major diagnostic and therapeutic challenges.
Keywords: liver cirrhosis; kidney function; HRS